2014
DOI: 10.1016/j.jfda.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effects of Camellia sinensis L. extract in patients with type 2 diabetes

Abstract: The prevalence of diabetes mellitus (DM) has dramatically increased in the past decade. Furthermore, increasing evidence from research shows that oxidative stress (OS) plays a crucial role in the pathogenesis of diabetes and in its complications. A search for ways to reduce oxidative damage has become the focus of interest for the majority of scientists. In this study, we determined the radical scavenging activity of single green tea constituents by using an on-line high performance liquid chromatography (HPLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 33 publications
2
31
0
4
Order By: Relevance
“…There are many bioactive components in tea showing antioxidant activity, including catechins [ 23 ], gallic acid [ 44 ] and polysaccharides [ 45 ]. EGCG, the most abundant catechin compound, is a potent antioxidant in GTE [ 46 ]. Tea polysaccharides are another group of antioxidants in tea, and their antioxidant activities depend on monosaccharide composition and molecular weight [ 47 ].…”
Section: Protective Effects Of Tea Against Dmmentioning
confidence: 99%
“…There are many bioactive components in tea showing antioxidant activity, including catechins [ 23 ], gallic acid [ 44 ] and polysaccharides [ 45 ]. EGCG, the most abundant catechin compound, is a potent antioxidant in GTE [ 46 ]. Tea polysaccharides are another group of antioxidants in tea, and their antioxidant activities depend on monosaccharide composition and molecular weight [ 47 ].…”
Section: Protective Effects Of Tea Against Dmmentioning
confidence: 99%
“…This result indicated that antioxidant compounds in the extracts are significantly able to reduce DPPH radical into its nonradical form DPPH-H. Therefore, our results suggested that tea extracts may be a promising source of antioxidant which may protect against diseases induced by radicals (Patlevič et al, 2016, Spadiene et al, 2014. Recent studies have highlighted the importance of polyphenolic compounds due to their importance in antioxidant activities and other biological activities (Makris et al, 2007).…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies suggest that EGCG, EGC, ECG, EC, and C are the major catechins in tea, with their antioxidant activities demonstrated in the following order: EGCG > ECG > EGC > EC > C (Li et al, ; Spadiene et al, ). It is widely recognized that polyphenols of different molecular structures present different antioxidant activities.…”
Section: Resultsmentioning
confidence: 98%